AN ONE BELT, ONE ROAD AND THE WORLD: HOW CHINA IS MASTERING THE WORLD'S MIGRATION PATTERNS - Rafsanjani Is Marus (Jurnal Ilmiah Kajian Keimigrasian, 2021)
This study looks at China's "One Belt, One Road" initiative, which is grouped into two parts: the Maritime Silk Road Initiative and the Silk Road Economic Belt, both of which were revealed in 2013. Through the establishment of interconnected infrastructure projects such as ports, roads, railways, and pipelines, each component has the ability to reshape the global geopolitical landscape.The paper is divided into four sections to help the reader have a better grasp of the OBOR project and its impacts. This study describes trends and patterns of recent OBOR projects in Belt and Road Countries, analyzes the geopolitical implications of the OBOR, and investigates the integration of new migration patterns based on existing data and literature on current Chinese development. Using a geopolitical approach that identifies territorial and political power, This study examined prospective migration and integration patterns that may emerge as the OBOR initiative advancements. As a result, this paper concludes that the OBOR initiative is not only an international cooperation project, but something that also turns China's geopolitics power at various levels, has the potential to be momentous, and will simultaneously create opportunities for global partnership while also reshaping the existing migration pattern and a new geopolitics perspective.